Firmware architecture of the back end DAQ system for the CMS high granularity endcap calorimeter detector. (1st April 2022) - Mallios, S.; Dauncey, P.; David, A.; Vichoudis, P.; ,
Abstract: During the High-Luminosity phase of the Large Hadron Collider, the endcap calorimeter detectors of the compact muon solenoid experiment will be replaced by the high-granularity calorimeter. For reading out the new calorimeter, field programmable gate array firmware was developed targeting the off-detector hardware. The firmware is responsible not only for the readout of the detector but also for its slow control and timing. To facilitate system maintenance, the firmware is optimized to handle all the different front-end electronics configurations and data rates using a single — highly configurable — design. This manuscript presents the firmware architecture and the implementation.